Circadian rhythms of ocular and systemic blood flow in patients with progressive primary open-angle glaucoma - Yuliya E. Filippova; Tatiana N. Malishevskaya; Denis G. Gubin; Ekaterina V. Renzyak; Ekaterina K. Zakharova (Russian Open Medical Journal, 2025)
Background — The significant role of hemodynamic factors in the pathogenesis of primary open-angle glaucoma (POAG) is now widely recognized. However, no studies have examined daily fluctuations in ocular and systemic blood flow in the context of endothelial dysfunction and their potential influence on the progression of glaucomatous optic neuropathy. This study aimed to assess daily variations in ocular and systemic hemodynamic parameters in POAG patients, focusing on their association with endothelial vasodilatory capacity. Material and methods — A total of 177 patients (350 eyes) were examined, including 99 patients with POAG (198 eyes; mean age 69.1±6.1 years), and 78 сontrol subjects without glaucoma (152 eyes, mean age 68.2±5.8 years). To evaluate circadian variations in ocular and systemic hemodynamics, we assessed ocular pulse via electrotonosphygmography, peripheral blood flow in the upper and lower extremities using sphygmomanometry, and subfoveal choroidal thickness (SFCT), an indicator of choroidal blood filling, measured with the choroidal protocol on the OCT-HS100 device. All measurements were performed by a single operator at 08:00, 14:00, and 20:00 over three consecutive days, with standardized nutritional and physical activity protocols. Data were analyzed using correlation and multiple regression analyses. Results — Our analysis of diurnal variations in ocular pulse and peripheral arterial blood flow (upper and lower extremities) revealed prominent, synchronized rhythmic oscillations in both glaucoma patients and age-matched controls. Peak blood flow velocities occurred in the morning hours, with lowest values observed in the evening. Patients with progressive glaucoma exhibited statistically significant reductions in pulse ocular blood flow and peripheral arterial perfusion, alongside elevated vascular resistance indices (PWV, CAVI, ABI, AI-R) compared to stable glaucoma cases and controls. Choroidal thickness variations demonstrated dependence on diurnal intraocular pressure (IOP) fluctuations. Vasodilatory capacity followed a circadian pattern in all groups, with maximal endothelial reactivity in the morning, progressive daytime decline, and minimal evening values. This decrease was significantly more prominent in progressive POAG (P-POAG) than in stable glaucoma or control groups. Conclusion — The observed similarity in diurnal variations of ocular pulse parameters and peripheral vascular blood flow may reflect circadian rhythms in hormonal and metabolic activity. Notably, impaired ocular pulse characteristics and reduced peripheral blood flow – particularly during late evening hours – were associated with marked endothelial dysfunction. These findings suggest that such hemodynamic disturbances may serve as prognostic markers for glaucoma progression.